Training Attention to the Other’s Need Improves Helping Behaviors in Children with Autism Spectrum Disorder: A Behavioral Analysis Using a Two-dimensional Motion Capture System - Kita, Yosuke; Gunji, Atsuko; Sakuma, Ryusuke; Goto, Takaaki; Okumura, Yasuko; Inagaki, Masumi (Frontiers in Education, 2017)
While children with autism spectrum disorder (ASD) can acquire helping behaviors through appropriate interventions, changes in behaviors prior to helping (pre-helping behaviors) remain unclear. In the present study, we examined the effects of social skills training (SST) on helping and pre-helping behaviors in two children with ASD by using a two-dimensional motion capture system. During the SST, the children learned one helping behavior that they lent their items to their partners, and we measured their head movements before initiating the helping behavior (i.e., pre-helping behavior). As a result of SST, the participants became able to help others in response to less explicit social stimuli after the intervention. Regarding pre-helping behaviors, the children with ASD before the intervention looked straight at the helpee (i.e., recipient of the help) more often than did typically-developing peers, and such a behavior was shown to increase after SST. These results indicate that although spontaneous attention to social stimuli may be reduced in children with ASD, success in attending to a helpee could lead to the emergence of helping behaviors. Moreover, the changes in pre-helping behavior indicate an increase in children’s attention to the helpee after the intervention, which may have enhanced their sensitivity to persons in need.